Vitamin C content in fruits of camu camu Myrciaria dubia (H.B.K) Mc Vaugh, in four states of maturation, coming from the Collection of Germoplasma of the INIA Loreto, Peru - Imán Correa, Sixto (2011)
The objective of the present work was to determine the vitamin content C in different parts from the fruit; pulp, rind and pulp more rind, in four states of maturation: green, mature green, mature and over mature. The fruits were obtained from the Collection of Germoplasma of the Agrarian Experimental Station San Roque of the INIA Loreto, Peru. The technique used for the determination of vitamin content C was Liquid High Chromatography Performance (HPLC) with phase column reverse. The results indicate that the greater vitamin contents C are in the rind and the states of over mature and mature. And vitamin C contained according to maturation states adjusts to a curve of cubical regression, as much for pulp, rind and pulp more rind with 87%, 90% and 98 % of effectiveness; respectively. When moving from a state of maturity to another, the vitamin C content is increased in 515.43 mg in each 100 g of rind sample. The obtained results indicate that camu camu is a potential vitamin C source, located mainly in the rind of the fruit.